Independent Learning from the Perspective of Educational Philosophy: A Critical Analysis of Contemporary Phenomena in Education in Indonesia - Fauzi, Azra; Tika, I Nyoman; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The “Merdeka Belajar” policy represents Indonesia’s transformative effort to create a more flexible, humanistic, and competency-oriented educational ecosystem aligned with 21st-century demands. This article aims to analyze the philosophical foundations underpinning the policy and to evaluate its alignment with practical implementation in schools. Using a library research method, the study examines scholarly works, policy documents, and international educational reports. The findings reveal that Merdeka Belajar is grounded in progressivism, constructivism, humanism, existentialism, social reconstructionism, and the educational philosophy of Ki Hajar Dewantara. However, its implementation continues to face challenges, including teacher readiness, infrastructural limitations, digital inequality, and governance issues. The critical analysis highlights a persistent gap between the policy’s philosophical ideals and practical realities, indicating the need for strengthened teacher training, equitable resource distribution, and increased community involvement. The study concludes that the success of Merdeka Belajar depends not only on curriculum design but also on collective commitment among educational stakeholders to ensure a liberating, inclusive, and future-relevant learning environment.